TRANSLATION SHIFTS IN RENDERING UZBEK CULTURAL TERMS INTO ENGLISH - Anna Müller (International Journal of Literature and Language Studies, 2026)
This article studies translation shifts used when Uzbek cultural terms are rendered into English. The study responds to the problem that culturally specific words are difficult to translate because literal equivalence may preserve form but fail to communicate social meaning to target readers. Using descriptive translation analysis comparing lexical, semantic, and cultural shifts, the article analyzes parallel excerpts from Uzbek literary prose and their English translations. The findings indicate that translators used borrowing, explanation, generalization, and cultural substitution depending on whether a term named food, kinship, clothing, ritual, or social status. The article argues that effective translation of cultural terms requires a flexible balance between foreignization and reader accessibility. By connecting language, literary form, and interpretation, the study offers a concise contribution to current debates in literature and language studies.